ASSESSMENT AND RELATIONSHIPS BETWEEN PHYSICAL AND ECONOMIC ACCESSIBILITY OF FOOD: STATUS AND FORECAST - Elena DERUNOVA; Natal’ya KIREEVA; Olesya PRUSCHAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article discusses various aspects of food security: the level of self-sufficiency, physical and economic accessibility of food. Methodical approaches to the assessment of food security are proposed: the physical availability of food through the coefficient of sufficiency of consumption of basic types of food (meat, milk, vegetables), economic affordability through the share of food costs in household expenditures. The values of various levels (permissible and critical) of food availability are substantiated. Based on the regression analysis, factors determining the physical and economic accessibility of food have been identified. The forecast of the level of achievement of the criteria of food security was fulfilled, which made it possible to estimate the timeframe and resource possibilities in terms of the main types of food. The dependence of the adequacy of consumption of basic food products to a greater degree on the increase in domestic production than on the external content of the food market has been revealed. It has been proven that physical accessibility does not always mean the economic accessibility of food. The degree of differentiation of individual subjects of the Volga Federal District of the Russian Federation on the level of economic and physical accessibility of food has been evaluated. It is concluded that there is an interconnection between various aspects of food security. The results of the study can be used to justify the priorities of the agri-food policy.